Mitochondrial DNA abundance in blood is associated with Alzheimer’s disease- and dementia-risk - Stocker, Hannah; Gentiluomo, Manuel; Trares, Kira; Beyer, Léon; Stevenson-Hoare, Joshua; Rujescu, Dan; Holleczek, Bernd; Beyreuther, Konrad; Gerwert, Klaus; Schöttker, Ben; Campa, Daniele; Canzian, Federico; et al. (Molecular psychiatry, 2025)
The mitochondrial cascade hypothesis of Alzheimer’s disease (AD) has been portrayed through molecular, cellular, and animal studies; however large epidemiological studies are lacking. This study aimed to explore the association of mitochondrial DNA copy number (mtDNAcn), a marker representative of mtDNA abundance per cell, with risk of incident all-cause dementia, AD, and vascular dementia diagnosis within 17 years and dementia-related blood biomarkers (P-tau181, GFAP, and NfL). Additionally, sex-stratified analyses were completed. In this German population-based cohort study (ESTHER), 9940 participants aged 50-75 years were enrolled by general practitioners and followed for 17 years. Participants were included in this study if information on dementia status and blood-based mtDNAcn measured via real-time polymerase chain reaction were available. In a nested case-control approach, a subsample of participants additionally had measurements of P-tau181, GFAP, and NfL in blood samples taken at baseline. Of 4913 participants eligible for analyses, 386 were diagnosed with incident all-cause dementia, including 130 AD and 143 vascular dementia cases, while 4527 participants remained without dementia diagnosis within 17 years. Participants with low mtDNAcn (lowest 10%) experienced 45% and 65% percent increased risk of incident all-cause dementia and AD after adjusting for age and sex (all-cause dementia: HRadj, 95%CI:1.45, 1.08-1.94; AD: HRadj, 95%CI: 1.65, 1.01-2.68). MtDNAcn was not associated to vascular dementia diagnosis and was more strongly associated with all-cause dementia among women. In the nested case-control study (n = 790), mtDNAcn was not significantly associated with the dementia-related blood biomarkers (P-tau181, GFAP, and NfL) levels in blood from baseline before dementia diagnosis. This study provides novel epidemiological evidence connecting mtDNA abundance, measured via mtDNAcn, to incident dementia and AD at the population-based level. Reduced mitochondrial abundance may play a role in pathogenesis, especially among women.
Online veröffentlicht: 15. Juli 2024
Gesehen am 27.01.2025